Newborns and Under-5 Mortality in Ethiopia: The Necessity to Revitalize Partnership in Post-COVID-19 Era to Meet the SDG Targets - Yonas Getaye Tefera; Asnakew Achaw Ayele (SAGE Publishing, 2021)
The Sustainable Development Goals (SDGs) were adopted during the United Nations meeting in 2015 to succeed Millennium Development Goals. Among the health targets, SDG 3.2 is to end preventable deaths of newborns and children under 5 years of age by 2030. These 2 targets aim to reduce neonatal mortality to at least as low as 12 per 1000 live births and under-5 mortality to at least as low as 25 per 1000 live births. Ethiopia is demonstrating a great reduction in child mortality since 2000. In the 2019 child mortality estimation which is nearly 5 years after SDGs adoption, Ethiopia's progress toward reducing the newborns and under-5 mortality lie at 27 and 50.7 per 1000 live births, respectively. The generous financial and technical support from the global partners have helped to achieve such a significant reduction. Nevertheless, the SDG targets for newborns and under-5 mortality reduction are neither attained yet nor met the national plan to achieve by the end of 2019/2020. The partnership dynamics during COVID-19 crisis and the pandemic itself may also be taken as an opportunity to draw lessons and spur efforts to achieve SDG targets. This urges the need to reaffirm a comprehensive partnership and realignment with other interconnected development goals. Therefore, collective efforts with strong partnerships are required to improve the determinants of child health and achieving SDG target reduction until 2030.